Permainan Kartu Zone 2000 Dalam Perspektif Istishlah - Munjid, Abdul; Hikmah , Nurul; Isnaini , Eli (El-Qenon: Journal of Islamic Law, 2024)
All laws established by Allah contain benefits, as every aspect of the law, whether a command or prohibition, provides advantages to humans. However, when humans encounter a problem for which there is no explicit sharia evidence, considerations of public welfare (maslahah) and the prevention of harm (mafsadah) become crucial in establishing the law. In its application as a legal argument, scholars are divided into two groups: first, scholars who accept istishlah as a legal argument with the condition that the benefits are real and not speculative, are general and not personal, and do not contradict sharia evidence. Second, scholars who reject the application of istishlah as a legal argument in establishing Islamic law. From the perspective of Islamic Law, playing the Zone 2000 card game, such as in Laris Temanggung, is seen more as entertainment or refreshing activity, so it is not considered contradictory to sharia because it is not done excessively. Considering the benefits to children, it can realize public welfare or avoid harm to humans and does not directly contradict sharia